Motivation behind Bicycling Habit in Sylhet City of Bangladesh - Nawaz, Taharat (Asian Business Review, 2015)
The study was conducted in the Sylhet City of Bangladesh. The purpose of the study is to explore the motivational factors behind bicycling habit in Sylhet. Analysis of secondary data and a focus group session with pioneer cyclists contributed in obtaining variables for the study. A sample of 100 respondents of Sylhet participated in this study. Judgemental sampling technique has been used to obtain data from self-administered structured questionnaire. Statistical analyses used in the survey are Exploratory Factor Analysis to identify factors and Frequencies for analysing demographic variables. The result of the study explains four factors. Findings show that the favorable factors towards cycling are Factor 1, Health and Factor 2, Convenience. Factor 3, Weather and Factor 4 Security are deterrent factors in cycling.The research findings provide wider scope for urban planning and catering of promotional strategies by bicycle marketers. In an overly populated country like Bangladesh, bicycling can give us a congestion free road and the plociy makers can grab this opportunity to make a better strategy for urban planning. JEL Classification Code: M31